An Optimization Solution Using A Harmony Search Algorithm - Mansor, Nur Farraliza; Abal Abas, Zuraida; Abdul Rahman, Ahmad Fadzli Nizam; Shibghatullah, Abdul Samad; Sidek, Safiah (SCIENCE INTERNATIONAL (LAHORE), 2014)
-